Prospective evaluation of a protocol for induction of sustained ventricular tachycardia in patients referred to a tertiary centre. Issue 4 (October 1990) - Griffith, M J; Linker, N J; Mehta, D; Ward, D E; Camm, A J
Abstract : All eight stages of a stimulation protocol that used one then two extrastimuli from the right ventricular apex in sinus rhythm and three ventricular drive rates (100, 120, and 140 beats/min) were performed in 24 patients with recurrent spontaneous sustained ventricular tachycardia despite drug treatment. Twenty two of the patients had sustained a previous myocardial infarct and 18 were on long term treatment with amiodarone. Sustained (greater than 30 s) ventricular tachycardia was induced in all patients. Two extrastimuli were significantly more likely to induce sustained ventricular tachycardia than one extrastimulus, both overall and individually for the three ventricular drive rates. A ventricular drive rate of 140 beats/min was significantly more likely to induce ventricular tachycardia than ventricular drive rates of 100 and 120 beats/min which were significantly more effective than sinus rhythm. A ventricular drive rate of 140 beats/min with one or two extrastimuli induced ventricular tachycardia in 23/24 (95%) of the patients in this study. The full eight stage protocol was progressive separately for both extrastimuli and ventricular drive rate but the last two stages (ventricular drive rate of 140 beats/min with one or two extrastimuli) were as effective as the entire protocol in inducing ventricular tachycardia.